Clinical and Molecular Characteristics of 60 Patients With Human Immunodeficiency Virus-Negative Castleman Disease - Qian, Siyu; Ding, Mengjie; Hou, Huting; Wang, Zeyuan; Zhang, Jieming; Zhang, Yue; Dong, Meng; Zhu, Linan; Wang, Guannan; Li, Wencai; Zhang, Xudong (Frontiers in Immunology, 2022)
Castleman disease (CD) is a rare lymphoproliferative disorder. The mechanistic target of rapamycin (mTOR) pathway is a key regulator of various cellular functions, which may be related with the potential mechanisms of CD occurrence. We retrospectively collected the clinical information of 60 CD patients diagnosed in the First Affiliated Hospital of Zhengzhou University. And FFPE biopsy specimens were collected from 31 patients (12 unicentric CD patients and 19 multicentric CD patients) to detect the mTOR pathway protein expression. We are the first to demonstrate that thrombocytopenia and hypoalbuminemia are independent poor prognostic factors for CD. Moreover, mTOR activation was higher in CD compared to reactive lymphoid hyperplasia (used as a control group). This study offers some elucidation for the management and treatment of CD patients.